PROFILE OF STORY PROBLEM SOLVING OF THE TANGENT LINE ON THE CIRCLE BY STUDENTS OF CLASS IX E SMPN 5 PALU - Indriyani Indriyani; Muh. Hasbi; Anggraini Anggraini; Baharuddin Baharuddin (JME (Journal of Mathematics Education), 2024)
Completion of story problems by students needs to be profiled so that teachers can know the description or description of students' abilities in solving story problems. This study aims to obtain a profile of the completion of the circle tangent story problem by students of class IX E SMPN 5 Palu. This type of research is descriptive research with a qualitative approach. Data were collected through written tests and interviews. The results of this study showed that SH was able to do the problem correctly as the steps of solving the story problem. Then the results of EZ's solution show that there is an unfinished solution so that the answer obtained is wrong. Then the results of FR's completion showed that he was unable to solve the problem as the steps of solving the story problem so that the answer obtained was incorrect. Based on the results of this study, the researcher draws the conclusion that the profile of solving students' story problems varies based on students' mathematical abilities.